Evolution and actual situation of pollution at the Mucuripe harbor embayment (Fortaleza-Ceará State, Brazil) - Vasconcelos, Fábio Perdigão; Melo, Maria Thereza Damasceno (Arquivos de Ciências do Mar, 2018)
The first studies on pollution in the Mucuripe Bay in 1979 showed high values (up to 8.1% dry weight) of anthropogenic pollutants, notably oil and grease in the sediments. Following the dredging works performed in period 1979-1989 in the harbor basin, the present situation seems to have improved. Sediment quality and distribution has not significantly changed and they are still dominated by fine grained sand. In the central area of the bay and near the harbor, the pollutant content has dropped down 0.51% dry weight, which still is over the acceptable levei according to international legislation. The low amounts of organic carbon in sediments associated with a high free oxygen chemical demand depict the domination of chemical oxydizing processes over biochemical ones. The water of the bay presents normal temperature, salinity and dissolved oxygen content values. No stratification has been noticed, but the decreasing dissolved oxygen content from surface to botton shows a high oxygen consumption at the water-sediment interface. From the analysed data, it seems that dredging produced a significant drop down of sediment pollution even though it increased again after- wards. Thus, in some cases, dredging may be an efficient and cheap solution to avoid oil and grease pollution in sediments in and around harbors.